Legal Study of Electricity Extension By PT. State Electricity Company In Merauke District - Erni Dwita Silambi; Nurwita Ismail (Faculty of Law, Musamus University, 2020)
PT. PLN as one of the business actors and also as a State-owned business entity should be able and as much as possible to provide electricity evenly and quality to its consumers. But in reality the community is still faced with various problems in the field of electricity. The method used in this study is the library method and field method. library method by reading books, journals and other literature while the field data is obtained by going down to the field to retrieve data then the data analyzed using qualitative methods will then be presented descriptively. The results of this study are PT PLN Merauke trying to provide electricity supply according to the needs of the community however, PLN is also forced to take turns by blackouts at certain times because they have to carry out maintenance and rejuvenation of the machines that have also replaced old electricity poles, but if there is a rotating power outage, PLN always announces the outage through social media. and also through RRI. People as electricity users have not been active and tend to accept and be quiet if they feel disadvantaged by a power outage.